2018
DOI: 10.1074/mcp.ra117.000315
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-resolved Proteomic Analysis of Mouse Aorta during Atherosclerotic Plaque Formation Reveals Osteoclast-specific Protein Expression

Abstract: Atherosclerosis leads to vascular lesions that involve major rearrangements of the vascular proteome, especially of the extracellular matrix (ECM). Using single aortas from ApoE knock out mice, we quantified formation of plaques by single-run, high-resolution mass spectrometry (MS)-based proteomics. To probe localization on a proteome-wide scale we employed quantitative detergent solubility profiling. This compartment- and time-resolved resource of atherogenesis comprised 5117 proteins, 182 of which changed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 83 publications
1
26
0
Order By: Relevance
“…We previously developed the quantitative detergent solubility profiling (QDSP) method to add an additional dimension of protein solubility to tissue proteomes 3133 . In QDSP, proteins are extracted from tissue homogenates with increasing stringency of detergents, which typically leaves ECM proteins enriched in the insoluble last fraction.…”
Section: Resultsmentioning
confidence: 99%
“…We previously developed the quantitative detergent solubility profiling (QDSP) method to add an additional dimension of protein solubility to tissue proteomes 3133 . In QDSP, proteins are extracted from tissue homogenates with increasing stringency of detergents, which typically leaves ECM proteins enriched in the insoluble last fraction.…”
Section: Resultsmentioning
confidence: 99%
“…In our investigation of the adult neurogenic niche (Kjell et al, 2020), also using the QDSP protocol, we found that ECM proteins, such as Tn-C, are more soluble compared to the brain parenchyma. Tn-C is also highly soluble in the scar region analyzed by QDSP at 28 dpi here, which is opposite to its insoluble nature in lung injury and atherosclerotic plaques (Schiller et al, 2015;Wierer et al, 2018). These are examples of how any quantification and information regarding ECM architecture would be lost without adopting a protocol that allows composition-dependent sample analysis.…”
Section: Monocyte-dependent Ecm In the Glial Scarmentioning
confidence: 87%
“…Alterations in ECM composition and possibly architecture in the aging lung have been suggested 25 , however experimental evidence using unbiased mass spectrometry is scarce. We previously developed the quantitative detergent solubility profiling (QDSP) method to add an additional dimension of protein solubility to tissue proteomes [26][27][28] . In QDSP, proteins are extracted from tissue homogenates with increasing stringency of detergents, which typically leaves ECM proteins enriched in the insoluble last fraction.…”
Section: Age Dependent Changes In Composition and Organization Of Thementioning
confidence: 99%